Marketing and Production Patterns of Skipjack Tuna (Katsuwonus pelamis) at the Coastal Fishing Port in South Halmahera Regency - Nasir Haya; Hardin; Julkarnain Ahmad; Asmaia Narju (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study aims to identify the marketing pattern and production of skipjack tuna (Katsuwonus pelamis) at the Coastal Fishing Port. The research employed a quantitative descriptive method using a survey approach. Data were collected through observation, interviews, documentation, and recording of skipjack tuna production and marketing data. The data were analyzed descriptively to describe the production conditions and marketing distribution patterns of skipjack tuna in the research area. The results showed that the production value of skipjack tuna in 2022 fluctuated monthly, with a total production value of IDR 84,114,227,500. The highest production value occurred in March, amounting to IDR 12,156,746,000, while the lowest production value was recorded in November, amounting to IDR 3,149,106,000. Production fluctuations were influenced by weather conditions, fishing seasons, fishermen's activities, and the availability of fish resources. The total volume of fish marketed during the study period reached 1,290.8 kg. The selling price of skipjack tuna was relatively stable at around IDR 23,000 per kilogram, although some areas experienced price differences depending on market conditions and distribution costs. The study concludes that the production and marketing of skipjack tuna play an important role in supporting the economy of coastal communities in South Halmahera Regency. Therefore, improvements in fisheries infrastructure and facilities, strengthening of the marketing system, and government support are needed to maintain the stability of fisheries production and distribution.